Analisis Kemampuan Keterampilan Dasar Mengajar (Micro Teaching) Mahasiswa Angkatan I Program Studi Pendidikan IPS Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasir Pengaraian - Welven Aida (Jurnal Edu Research, 2019)
The purpose of this study was to determine the basic skills of Micro Teaching for first year students in the Social Sciences study program FKIP UPP T.A 2018/2019. The basic components of micro teaching skill is the basic skill to students who are going to be a teacher. Micro teaching is a course to practice teaching in faculty of teacher training and education. This research was conducted in first year students in social studies education study programs.The methodology of this research is qualitative research. The researcher uses the teacher instrumentation assessments (IPKG 2). From the analysis, it can be concluded that the basic components of micro teaching skill in first year students in social studies education students of FKIP in Universitas Pasir Pengaraian is in good category or in 58,82 % .